Systematic Yeast Two-Hybrid Analysis of Human E2 Ubiquitin-Conjugating Enzyme and Deubiquitin (DUB) Protein Interactions - Zulkifle, Nurulisa (Academic Journals Inc., 2013)
Post-translational modification of proteins via ubiquitination is mediated by three enzyme families; El activating enzymes, E2 conjugating enzymes and E3 ligases, all of which work in a hierarchical manner to facilitate different forms of protein ubiquitin ranging from mono-ubiquitination to the formation of different forms of ubiquitin chains. Reversibly, deubiquitinating enzymes (DUBs) act to remove ubiquitin from modified substrates. Apart from the classic interactions within the E1-E2-E3 enzymatic cascade, an unusual non-hierarchical interaction has been observed between some E2 enzymes and a DUB called Otubain-1 (OTUB1). This observation raises interesting questions concerning the order and specificity within the human ubiquitin system. In this study, systematic yeast two-hybrid (Y2H) binary screen is performed between 39 E2 and 60 DUB proteins to analyze the extent of human E2-DUB interactions. As a result, putative partnerships between OTUB1 and UBE2D1, UBE2D2, UBE2D3, UBE2D4, UBE2E1, UBE2E2, UBE2E3 and UBE2N are identified and these data correlate well with data from other independent study by high-throughput Y2H library screen and mass spectrometry. In essence, this study confirmed that E2-DUB interactions within the human ubiquitin system are indeed uncommon and only unique to OTUB1 protein.